2000
DOI: 10.1182/blood.v95.1.277.001k45_277_285
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Rel/NF-κB and octamer factors is a hallmark of the generation and maturation of dendritic cells

Abstract: A key feature of maturation of dendritic cells is the down-regulation of antigen-processing and up-regulation of immunostimulatory capacities. To study the differential expression of transcription factors in this process, we investigated the nuclear translocation and DNA binding of Rel/NF-κB and octamer factors during in vitro generation and maturation of dendritic cells compared with macrophage development. RelB was the only factor strongly up-regulated during the generation of both immature dendritic cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…Cluster analysis further showed that maturation-induced DCs (G4T and G4CD40L) had increased expression of helix±loop± helix id2, c-rel, IRF-4, HOX-5 and BTG-1 transcription factors. Our observation of increased c-rel expression following maturation induction confirms a previous study of human dendritic cells (Neumann et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Cluster analysis further showed that maturation-induced DCs (G4T and G4CD40L) had increased expression of helix±loop± helix id2, c-rel, IRF-4, HOX-5 and BTG-1 transcription factors. Our observation of increased c-rel expression following maturation induction confirms a previous study of human dendritic cells (Neumann et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…A variety of microbial ligands have been shown to activate immune responses via mammalian Toll-like receptors (TLRs) [21]. Monocyte-derived DCs express TLR 1,2,4,5,8 [22]. Several groups have shown that preparations of Gram-positive bacteria mediate cellular signaling via TLR2.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Fgl2-induced inhibition of DC and B cell functions, FcγRIIB phosphorylation was not observed, suggesting that the signaling is triggered in an ITIMindependent manner (46). As an alternative, soluble Fgl2 could block NF-κB translocation into nucleus, resulting in the down-regulation of CD80 and MHC II expression on DCs (13) and likely their maturation (52,53). Finally, data is emerging that shows that Fgl2 regulates adaptive immunity via Th1 and Th2 cytokines.…”
Section: Fgl2 Inhibits DC Maturationmentioning
confidence: 99%